Development of Accounting in Iranian Universities - Mahdi Piri Sagharloo (University of Tehran, 2021)
Objective: The purpose of this study is to try to understand the emergence and development of Academic accounting in Iran and the role played by Iranian universities in this regard, as well as how to develop Academic accounting education in Iran and finally compare the development of Academic accounting teaching with countries in the region and the impact of academics and universities. The West, especially the United States of America and England, is in the field of Academic accounting in Iran.Methods: The research method of the present study is qualitative (oral history with content analysis approach), interpretive research paradigm and research method from the perspective of exploratory purpose. The method of data collection is unstructured interviews with experts who have played an important role in the emergence and development of accounting in Iranian universities. The stages of this research include compiling research questions, data collection, data encryption, writing analytical notes, recording ideas and interpreting data, writing and compiling a documentary history of the development of academic accounting in Iran.Results: The results led to the formation of a category communication network in which 30 main categories related to the development of accounting education in Iranian universities were identified and explained. Also, based on the interviews, specific answers were given to the main research questions and the development of Academic accounting education in Iran was clarified.Conclusion: Academic accounting education has undergone extensive changes in Iran since its inception until today and it can be said that modern accounting is a product of the university and this role in Iran has become more colorful since the creation of postgraduate courses. The results indicate that in general, thirty factors have played a role in shaping the current face of Academic accounting in Iran. Experts believe that Academic accounting education and research in Iran owes much to Western countries, especially the United States and the United Kingdom, and has a higher quantity and quality compared to neighboring countries in the region. Most of the interviewees are worried and dissatisfied with the state of Iran's higher education system. They believe that education in Iran does not have its real place and usually other factors and goals other than education are superior to Iran's higher education system. Therefore, according to the current situation, the quality of education in universities has gradually declined and other factors such as commercial, political, economic, etc. approach play a role and require proper management of the education system at the macro level of the country.